2019
DOI: 10.3390/agriculture9120255
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Fumigation and Bacillus Subtilis-Based Biofungicide on the Microbiome of Chrysanthemum Rhizosphere

Abstract: Chrysanthemum is an important ornamental species in China. However, sustained monoculture often leads to a decline in soil quality, in particular to the build-up of pathogens. Fusarium wilt, a severe disease in chrysanthemum monoculture systems, was effectively controlled by fumigation and/or the application of a biofungicide in our previous study. However, the mechanisms underlying disease suppression remain elusive. Here, a series of greenhouse experiments were conducted to characterize the effect on the chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this regard, Zhimo et al [5] reported a similar reduction in the richness of the fungal community in strawberry fruit treated with M. fructicola. The reduction in fungal diversity following the application of biological control agents has also been reported in other crops, such as tea (Camellia sinensis) leaves, as a result of the application of Serendipita (=Piriformospora) indica [24], and in the rhizosphere of chrysanthemum (Chrysanthemum morifolium) following the application of Bacillus subtilis NCD-2 [25]. In contrast, under natural conditions of cold storage, the diversity of microbes has been shown to increase with time [26], and our result also showed marginal increases in diversity with an increase in storage time in untreated fruit as compared with water-treated or biocontrol-treated fruit, where the diversity remained stable.…”
Section: Discussionmentioning
confidence: 70%
“…In this regard, Zhimo et al [5] reported a similar reduction in the richness of the fungal community in strawberry fruit treated with M. fructicola. The reduction in fungal diversity following the application of biological control agents has also been reported in other crops, such as tea (Camellia sinensis) leaves, as a result of the application of Serendipita (=Piriformospora) indica [24], and in the rhizosphere of chrysanthemum (Chrysanthemum morifolium) following the application of Bacillus subtilis NCD-2 [25]. In contrast, under natural conditions of cold storage, the diversity of microbes has been shown to increase with time [26], and our result also showed marginal increases in diversity with an increase in storage time in untreated fruit as compared with water-treated or biocontrol-treated fruit, where the diversity remained stable.…”
Section: Discussionmentioning
confidence: 70%
“…This resistance can necessitate increased pesticide application, which in turn can have detrimental effects on soil health, human well-being, and the overall environment [ 93 ]. (2) Reduced fertility: pesticides can negatively impact soil fertility by harming beneficial microorganisms responsible for maintaining soil health and nutrient levels [ 129 , 130 ]. (3) Pesticides can also have adverse effects on the diversity of microorganisms in the soil, resulting in a loss of biodiversity and a decline in the overall health and productivity of the ecosystem.…”
Section: Agronomic Practices Phytomicrobiomes and Plant Diseasesmentioning
confidence: 99%
“…Meng et al (2019) found that dazomet fumigation affected primarily the characteristics of fungi, and could reduce the number of Fusarium oxysporum-a pathogenic bacteriumand improve the yield of watermelon. Chen et al (2019) found that dazomet fumigation reduced significantly the number of bacteria and fungi in replanted soil and controlled chrysanthemum fusarium wilt effectively. 1,3-Dichloropropene, a soil fumigant and nematicide, is used primarily for strawberries, sweetpotatoes, melons, flowers, and other crops before planting, soil fumigation, and processing; it has been shown to be effective in controlling worms, plant pathogenic bacteria, and weeds (Qiao et al, 2010).…”
mentioning
confidence: 98%